Influence of Economic Indicators on Supply Chain: Evidence from Indonesian Fishing Industry - Yusro Hakimah; Siti Komariah Hildayanti; Aandhyka Tyaz Nugraha (International Journal of Supply Chain Management, 2019)
The supply chain dynamics has been broadly examined and experienced by the academes, industrialists as well as economists. However, still the literature is missing with the effect of economic indicators on supply chain practices, particularly in fishing industry. Therefore, the objective of the current study is to examine the role of economic indicators on supply chain in fishing industry of Indonesia. Fishing industry is one of the industries which is working from many centuries and now growing rapidly and considered to be the important element of economic growth in different countries like Indonesia. Six hypotheses were formulated with the help of previous studies, concerning the relationship between inflation rate, interest rate, human development index (HDI), gross domestic product (GDP) and supply chain. GDP was considered as the mediating variable. Managerial employees of fishing companies were selected as the respondents of this study. Primary data was collected by conducting the questionnaire survey. Total number of one hundred and ninety-six (196) response were received. These responses were analysed with the help of statistical software namely; Partial Least Square (PLS). It was found that economic indicators have influence on supply chain. Increases in inflation rate and interest rate decreases the supply chain. However, increases in HDI enhances the GDP and promote supply chain activities. Additionally, GDP is a mediating variable between HDI and supply chain which positively enhances the supply chain through HDI. Thus, study provides the clues for government to promote supply chain by controlling inflation and interest rate.